The clinical value of autologous platelet-rich plasma extraction and injection as an adjunct to urethroplasty in the treatment of penile hypospadias in children - Shang, Xianhui; Zhang, Zhendong; Mao, Kaiyi; Tang, Hongyanng; Zhou, Guangxu; Mao, Yuchen; Li, Yingbo; Luo, Zhen; Zhao, Peng; Wang, Cao; Ma, Hong (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the clinical efficacy and safety of autologous platelet-rich plasma (PRP) as an adjunctive treatment for penile hypospadias repair in children, and to explore its independent role in reducing postoperative complications.MethodsWe retrospectively analyzed clinical data from 103 pediatric patients undergoing penile hypospadias repair between December 2019 and December 2021 at the Affiliated Hospital of Zunyi Medical University. All patients received standard penile straightening and tubularized incised plate (TIP) urethroplasty. Patients in the study group (n = 53) additionally received intraoperative autologous PRP injections, whereas the control group (n = 50) did not. Outcomes analyzed included operation time, postoperative ambulation time, pain scores, length of hospital stay, incision infection rates at postoperative day 7, surgical success rates, and incidence of complications within 2 years postoperatively. Statistical analyses incorporated 95% confidence intervals (CIs), effect sizes (Cohen's d and relative risk, RR), and multivariate logistic regression analyses adjusting for potential confounders such as patient age and hypospadias severity.ResultsNo significant differences were observed between groups regarding operation time, postoperative ambulation time, or length of hospital stay (p > 0.05). Patients in the PRP group experienced significantly reduced postoperative pain (mean difference −2.14; 95% CI: −2.46 to −1.81; p < 0.001; Cohen's d = 2.35) and notably lower incision infection rates on postoperative day 7 (RR = 0.13; 95% CI: 0.03–0.60; p = 0.006). Surgical success rates were significantly higher in the PRP group compared to controls (94.3% vs. 72.0%; RR = 1.31; 95% CI: 1.09–1.58; p = 0.002). Multivariate logistic regression analysis confirmed that PRP injection remained independently associated with a significant reduction in postoperative complications after adjusting for age and severity of hypospadias (adjusted OR = 0.14; 95% CI: 0.04–0.52; p = 0.003).ConclusionAdjunctive autologous PRP treatment in pediatric penile hypospadias repair effectively alleviates postoperative pain, enhances wound healing, significantly reduces short-term complications, and improves surgical success rates. Future randomized, multicenter trials with extended follow-up periods are required to further evaluate long-term outcomes and to compare PRP efficacy directly with other biomaterials used in urethroplasty.